Clinical evaluation of an immunochromatographic IgM/IgG antibody assay and chest computed tomography for the diagnosis of COVID-19 (2020)
Background We evaluated the clinical performance of an immunochromatographic (IC) IgM/IgG antibody assay for severe acute respiratory syndrome coronavirus 2 (SARS-CoV2) and chest computed tomography (CT) for the diagnosis of Coronavirus disease 2019 (COVID-19). Methods We examined 139 serum specimens collected from 112 patients with COVID-19 and 48 serum specimens collected from 48 non-COVID-19 patients. The presence of IgM/IgG antibody for SARS-COV2 was determined using the One Step Novel Coronavirus (COVID-19) IgM/IgG Antibody Test. Chest CT was performed in COVID-19 patients on admission. Findings Of the139 COVID-19 serum specimens, IgM was detected in 27.8 %, 48.0 %, and 95.8 % of the specimens collected within 1 week, 1–2 weeks, and >2 weeks after symptom onset and IgG was detected in 3.3 %, 8.0 %, and 62.5 %, respectively. Among the 48 non-COVID-19 serum specimens, 1 generated a false-positive result for IgM. Thirty-eight of the 112 COVID-19 patients were asymptomatic, of whom 15 were positive for IgM, and 74 were symptomatic, of whom 22 were positive for IgM and 7 were positive for IgG. The diagnostic sensitivity of CT scan alone and in combination with the IC assay was 57.9 % (22/38) and 68.4 % (26/38) for the asymptomatic patients and 74.3 % (55/74) and 82.4 % (61/74) for the symptomatic patients, respectively. Conclusion The IC assay had low sensitivity during the early phase of infection, and thus IC assay alone is not recommended for initial diagnostic testing for COVID-19. If RT-qPCR is not available, the combination of chest CT and IC assay may be useful for diagnosing COVID-19.